Twitter and the politics of representation in South Africa and Zimbabwe’s xenophobic narratives during the covid-19 pandemic - Elizabeth Hove (Acta Academica, 2022)
The article analyses xenophobic narratives on Twitter in South Africa and Zimbabwe during the Covid-19 pandemic from March 2020 to July 2021. The study uncovers the politics of representation through discourse analysis of purposively sampled tweets. The article argues that xenophobic views perpetuated on Twitter during the Covid-19 pandemic period had the potential to influence negative attitudes towards Zimbabwean and other immigrants in South Africa. I show that Twitter was used as a platform to disseminate negative representations of Zimbabwean and other immigrants in South Africa. Political leaders on both sides of the border also utilised these representations to maintain their power. On the other hand Twitter played a critical part in mending the rift between Zimbabwean immigrants and some South Africans as it opened up communication between mainstream culture and other cultures. Regardless of this, social media platforms such as Twitter must be monitored and researched to understand the dynamics of representation of others, registering the need to respect and honour the constitutionally recognised freedom of expression.